Influence of mortar resistivity on the rate-limiting step of chloride-induced macro-cell corrosion of reinforcing steel. (September 2016) - Hornbostel, Karla; Angst, Ueli M.; Elsener, Bernhard; Larsen, Claus K.; Geiker, Mette R.
Highlights: The basic processes of macro-cell corrosion are not directly related to resistivity. Local conditions at the anode have a significant influence on the corrosion process. Consequently, no direct correlation exists between concrete resistivity and corrosion rate. Abstract: The influence of bulk resistivity on the kinetics of chloride-induced macro-cell corrosion of reinforcement was experimentally studied. It was found that the corrosion process was limited by a combination of anodic, ohmic and cathodic control for the geometrical conditions tested (anodes Ø 6 mm, cathode-to-anode ratio 685). The cathodic partial process was independent of the bulk resistivity. Both the anodic and the ohmic partial processes were influenced by local conditions around the anode but were not directly related to the bulk resistivity. The findings indicate that a unique relationship does not exist between bulk concrete resistivity and the corrosion rate.